The Future of mariculture: a regional approach for responsible development in the Asia-Pacific region FAO/NACA regional workshop, 7-11 March 2006, Guangzhou, China - Lovatelli, Alessandro; Phillips, Micheal J.; Arthur, J. Richard; Yamamoto, Koji; Food and Agriculture Organization of the United Nations; Network of Aquaculture Centres in Asia-Pacific. (Rome Food and Agriculture Organization of the United Nations, 2008)
Aquaculture in the Southeast Asian region has been growing steadily over the last few decades, requiring more space to accommodate it. The search for additional areas to expand the aquaculture industry as a whole and the identification of new farming species of commercial value to satisfy the growing local and export market are pushing the sector in some countries to broaden activities in the sea.--Publisher's description.
Bangladesh; People's Republic of China; Hong Kong; India; Indonesia; Islamic Republic of Iran; Japan; Republic of Korea; Malaysia; The Philippines; Thailand; Viet Nam; Pacific Islands.
Thematic regional reviews -- Country experiences -- Special presentations and perspectives.
Keywords: Mariculture -- Pacific Area -- Congresses